Haplotype-based analysis distinguishes maternal-fetal genetic contribution to pregnancy-related outcomes. - Amit K Srivastava; Julius Juodakis; Pol Sole-Navais; Jing Chen; Jonas Bacelis; Kari Teramo; Mikko Hallman; Pal R Njølstad; David M Evans; Bo Jacobsson; Louis J Muglia; Ge Zhang (PLoS Genetics)
Genotype-based approaches for the estimation of SNP-based narrow-sense heritability ([Formula: see text]) have limited utility in pregnancy-related outcomes due to confounding by the shared alleles between mother and child. Here, we propose a haplotype-based approach to estimate the genetic variance attributable to three haplotypes - maternal transmitted ([Formula: see text]), maternal non-transmitted ([Formula: see text]) and paternal transmitted ([Formula: see text]) in mother-child pairs. We show through extensive simulations that our haplotype-based approach outperforms the conventional and contemporary approaches for resolving the contribution of maternal and fetal effects, particularly when m1 and p1 have different effects in the offspring. We apply this approach to estimate the explicit and relative maternal-fetal genetic contribution to the phenotypic variance of gestational duration and gestational duration-adjusted fetal size measurements at birth in 10,375 mother-child pairs. The results reveal that variance of gestational duration is mainly attributable to m1 and m2 ([Formula: see text]). In contrast, variance of fetal size measurements at birth are mainly attributable to m1 and p1 ([Formula: see text]). Our results suggest that gestational duration and fetal size measurements are primarily genetically determined by the maternal and fetal genomes, respectively. In addition, a greater contribution of m1 as compared to m2 and p1 ([Formula: see text]) to birth length and head circumference suggests a substantial influence of correlated maternal-fetal genetic effects on these traits. Our newly developed approach provides a direct and robust alternative for resolving explicit maternal and fetal genetic contributions to the phenotypic variance of pregnancy-related outcomes.